Hanumante River: emerging uses, competition and implications - Sada, Rajesh (Journal of Science and Engineering, 2012)
This paper describes the existing uses and competition over Hanumante River water and its implications to the river ecology. The study was completed by conducting in-depth review of literatures, key-informants’ interview and semi-structured interview. The major water extraction in the Hanumante River is through 148 community drinking water supply schemes which is estimated to extract 15.6 million litres of water per day. Besides this, there are 127 irrigation systems with cumulative command area of 5174 ha in wet season and 42 brick industries using 142 million litres of water annually directly from Hanumante River, leaving very little water to flow downstream reaches. Moreover, there are hundreds of water pumps used for water extraction from river for irrigation purpose. The water flow on the downstream is essentially sewage flow and liquid wastewater disposal into the river and limited groundwater contributions. In addition, there are 232 industries in the city of Bhaktapur, most of which, although, do not extract river water directly, the effluents produced in these industries are discharged into the river either directly or through municipal sewerage system. In order to maintain the healthy river ecology, minimum environmental flow should be maintained in the river.